KONDISI OPTIMUM PERLAKUAN AWAL DAN PENGERINGAN KULIT BUAH NAGA KERING - Mulia W. Apriliyanti; Muhammad A. Suryanegara; Agung Wahyono; Siti Djamila (Jurnal Teknologi dan Industri Pangan, 2020)
Antioxidant plays an important role in keeping the body health. Antioxidant is needed to prevent the occurrence of oxidative stress, which causes of various degenerative diseases. Betacyanin in the dragon fruit peel takes part in antioxidant activity. The research is conducted using the central composite design (CCD) of the response surface methodology (RSM). This research aims to optimize the initial treatment condition by applying natrium metabisulfite immersion and drying on the dried dragon fruit peel. Three design composite factors used are natrium metabisulfite concentration (X1: 0.2-0.4%), drying temperature (X2: 65-75°C), and drying duration (X3: 4-5 hours) with betacyanin content (Y1) and antioxidant activity (Y2) as the response. A quadratic model is a method chosen for this research. The surface response showed the natrium metabisulfite concentration, temperature, and drying duration had signifi-cant effects on the betacyanin content and antioxidant activity. The most optimum condition of initial treatment is showed by immersion in 0.23% natrium metabisulfite and drying temperature of 70°C for 4.5 hours which resulted in 44.07 mg/100 g of betacyanin concentration and 50.56% antioxidant activity.